Der Funktionszustand der Wirbelsäule: Anforderungskriterien an Analysekonstruktionen - Schmitz, K.; Polinski, K. (Messplätze, Messplatztraining, motorisches Lernen: ausgewählte Beiträge; 5. gemeinsames Symposium der dvs-Sektionen Biomechanik, Sportmotorik und Trainingswissenschaft; Universität Leipzig, Sportwissenschaftliche Fakultät, 19. bis 21. September 2002 / Veranst.: Sportwissenschaftliche Fakultät der Universität Leipzig ..., 2003)
Introduction: Deficits in the stabilising musculature are considered to be an important risk factor for chronic back disorders. For years different treatment concepts have been admistered in the active therapy of functional backaches. In addition to the multiplicity of physiotherapy and the backside training models, analytic backed apparative treatmens have been established. Based on training science methods the functional status of the vertebral column (mobility, isometric strenght, dynamic endurance) will be fixed. Method: To warranty premium quality standards transparent preconditions of the equipment, measuring technique and reference data must be available. The consideration of the basic and auxiliary quality criteria, standardisation of the trial journal and the qualification of the supervisor, assure informative analysis results. The reporting of the identified parameters follows a standardisation, whilst the interpretation and the end-definition have to be individualised. Discussion: The analysis execution of the vertebral column stabilising musculature is only feasible in strong consideration of the existing indicators/contra-indicators. The discribed analysis construction is used alternatively in the activity diagnostics for different sports (golf, alpine ski, cycling).